Integrated Antennas on MnM Interposer for the 60 GHz Band - Lé, J. E. G.; Ouvrier-buffet, M.; Gomes, L. G.; Penchel, R. A. [UNESP]; Serrano, A. L. C.; Rehder, K. G. P. (Sociedade Brasileira de Microondas e Optoeletrônica e Sociedade Brasileira de Eletromagnetismo, 2022)
In this article, antennas for the 60 GHz ISM band designed to be integrated to a new high-frequency, low-cost interposer technology called Membrane-nanowire-Membrane (MnM) are discussed, manufactured, and measured. Also, an antenna characterization system under development at the Microelectronic Laboratory (LME-USP) is introduced, showing promising results for the deployment of mmW systems.
Keywords: 3D integration; interposer; patch; quasi-yagi; antenna characterization system